2018
DOI: 10.1002/prp2.378
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin as a potential therapy for the treatment of systemic infections: a population pharmacokinetic model to simulate multiple dosing regimens

Abstract: Fosfomycin has emerged as a potential therapy for multidrug‐resistant bacterial infections. In most European countries, the oral formulation is only approved as a 3 g single dose for treatment of uncomplicated cystitis. However, for the treatment of complicated systemic infections, this dose regimen is unlikely to reach efficacious serum and tissue concentrations. This study aims to investigate different fosfomycin‐dosing regimens to evaluate its rationale for treatment of systemic infections. Serum concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…It is unclear to what extent plasma and/or urine levels are decisive for efficacy in the step-down treatment of fUTIs. Higher oral doses up to 6–12g per day are expected to be needed for the empiric treatment of systemic infections [ 26 , 27 ]. We decided to dose fosfomycin at 3g every 24 hours because we anticipated that higher doses would not be tolerated [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear to what extent plasma and/or urine levels are decisive for efficacy in the step-down treatment of fUTIs. Higher oral doses up to 6–12g per day are expected to be needed for the empiric treatment of systemic infections [ 26 , 27 ]. We decided to dose fosfomycin at 3g every 24 hours because we anticipated that higher doses would not be tolerated [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…pathogens (5,6). Fosfomycin is an old antibiotic developed in the 1960s prior to modern methods for new antibiotic approval (7). It has a broad spectrum of activity that includes excellent activity against MDR Gram-negative pathogens such as extendedspectrum ␤-lactamase (ESBL)-producing organisms and carbapenem-resistant Enterobacterales (CRE) (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The model showed a good ability to characterise fosfomycin PK based on model diagnostics and validation. Most other recent studies also confirmed that the two-compartment model was the best fit to describe the fosfomycin plasma PK [17][18][19][20]. The second exponential decay suggests a distribution into deeper tissue, which leads to a slower release into plasma.…”
Section: Discussionmentioning
confidence: 69%
“…Although a number of studies on the population PK of fosfomycin have been conducted, most of these focused on plasma PK. Consequently, urinary PK is not fully understood [17][18][19][20]. Only a limited number of PK studies have evaluated plasma and urine samples simultaneously in healthy volunteers, utilising conventional PK analyses that did not include a covariate analysis [21][22][23].…”
Section: Introductionmentioning
confidence: 99%